2017
DOI: 10.5847/wjem.j.1920-8642.2017.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and anxiety pertaining to basic life support and medical emergencies among dental interns in Mangalore City, India

Abstract: BACKGROUND:This cross-sectional study aimed to assess the knowledge, attitude and anxiety pertaining to basic life support (BLS) and medical emergencies among interns in dental colleges of Mangalore city, Karnataka, India. METHODS:The study subjects comprised of interns who volunteered from the four dental colleges. The knowledge and attitude of interns were assessed using a 30-item questionnaire prepared based on the Basic Life Support Manual from American Heart Association and the anxiety of interns pertaini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 15 publications
2
15
0
5
Order By: Relevance
“…This compares to figures reported in other studies; 56% of dental interns in Southern India had BLS training (Elanchezhiyan et al, 2013), a report from Nigeria documented that 58% final year students had received medical emergency training (Ehigiator, Ehizele, & Ugbodaga, 2014), an Indian study reported that three quarters of dental interns had received some ME training (Abraham & Afradh, 2016), and approximately six in 10 dentists in a Brazilian study had undergone CPR training (Arsati et al, 2010). It is noteworthy that the majority of dentists and dental students feel that they require more training in BLS and MEs and have a positive attitude to learning these skills (Abraham & Afradh, 2016;Mwita et al, 2017;Somaraj et al, 2017). This is reflected in the present cohort where 83.5% of participants were willing to do further ME training.…”
Section: Discussionmentioning
confidence: 55%
“…This compares to figures reported in other studies; 56% of dental interns in Southern India had BLS training (Elanchezhiyan et al, 2013), a report from Nigeria documented that 58% final year students had received medical emergency training (Ehigiator, Ehizele, & Ugbodaga, 2014), an Indian study reported that three quarters of dental interns had received some ME training (Abraham & Afradh, 2016), and approximately six in 10 dentists in a Brazilian study had undergone CPR training (Arsati et al, 2010). It is noteworthy that the majority of dentists and dental students feel that they require more training in BLS and MEs and have a positive attitude to learning these skills (Abraham & Afradh, 2016;Mwita et al, 2017;Somaraj et al, 2017). This is reflected in the present cohort where 83.5% of participants were willing to do further ME training.…”
Section: Discussionmentioning
confidence: 55%
“…Another study conducted by Vinej et al ., evaluating the dental interns in a subpopulation of India, showed that there was an obvious lack of knowledge related to the management of medical emergencies. Data from the study revealed that 39.89% had below average knowledge regarding BLS [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with fi ndings reported in Bahrain and Ireland. [26,27] The skills which no students performed correctly in this study included checking responsiveness, checking breathing, performing highquality compressions, placement of the hand during BLS, the required number of compressions per minute, and the correct rate of compressions.…”
Section: Discussionmentioning
confidence: 95%